MECHANICAL SYSTEM FOR WIRE ARC ADDITIVE MANUFACTURING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
This article discusses the reassembly of a mechanical system for 3D printing plastic parts to be used for plasma arc additive manufacturing. The main issues in converting an existing 3D printer designed for plastic additive to used for producing metal parts are: control of the welding power source; installation and realization of the movement with the welding torch; set the height of the zero layer; setting up the program software to generate the control file.